2019
DOI: 10.33087/jiubj.v19i1.493
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Karakteristik Perawat terhadap Pelaksanaan Sasaran Keselamatan Pasien Pasca Akreditasi Rumah Sakit “X” di Kota Palembang Tahun 2018

Abstract: Safety of patients, nurses, companions and visitors is the main priority of nursing services in hospitals, because quality services will have an impact on hospital accreditation assessments. This study aims to determine the relationship between the characteristics of nurses on the implementation of patient safety goals after accreditation of "X" hospital in the city of Palembang in 2018. This research is descriptive using quantitative methods with sampling techniques using purposive sampling consisting of 96 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…It takes patience, patience, and compassion in the work of nurses. Surahmat et al, (2019) stated that gender does not affect the ability to learn and act. There is no difference between men and women in carrying out patient safety because they have the same responsibilities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It takes patience, patience, and compassion in the work of nurses. Surahmat et al, (2019) stated that gender does not affect the ability to learn and act. There is no difference between men and women in carrying out patient safety because they have the same responsibilities.…”
Section: Resultsmentioning
confidence: 99%
“…Gender does not affect the ability to learn and act. There is no difference between men and women in carrying out patient safety because they have the same responsibilities (Surahmat et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Length of work is categorized into two, namely the length of work of the new category ≤ 3 years and the old working time category> 3 years 12 . The results of previous studies found that the majority of nurses who had not worked long ago were ≤ 2 years and there was no significant relation between the length of nurses working with adherence to the implementation of SPO patient safety targets 13 .…”
Section: The Relation Between Nurse's Working Period and Compliance I...mentioning
confidence: 91%
“…Jenis kelamin tidak mempengaruhi dalam kemampuan untuk belajar dan bertindak. Tidak ada perbedaan laki-laki dan perempuan dalam melaksanakan keselamatan pasien karena memiliki tanggung jawab yang sama (Surahmat et al, 2019).…”
Section: Metodeunclassified